The Association of Anti-Aminoacyl-Transfer Ribonucleic Acid Synthetase Antibodies in Patients With Rheumatoid Arthritis and Interstitial Lung Disease - Masakazu MATSUSHITA; Naoto TAMURA; Michihiro OGASAWARA; Kurisu TADA; Ken YAMAJI; Yoshinari TAKASAKI (Archives of Rheumatology, 2018)
Objectives: This study aims to analyze the distribution and clinicopathological characteristics of anti-aminoacyl-transfer ribonucleic acid (tRNA) synthetase (ARS) antibodies in rheumatoid arthritis patients. Patients and methods: We retrospectively studied the anti-ARS antibody levels in 228 RA patients’ (44 males, 184 females; mean age 62.9±14.0 years; range 23 to 88 years) sera from their medical charts. We determined the association with anti-cyclic citrullinated peptide antibody levels, interstitial lung disease (ILD), rheumatoid factor, and methotrexate or biological disease modifying antirheumatic drug treatments. Results: Anti-ARS antibodies were detected in 14 RA patients (6.1%). ILD complications were significantly higher among anti-ARS antibody-positive patients (57.1% vs 22.4%, p<0.05). Levels of anti-threonyl-tRNA-synthetase (anti-PL-7) and anti-alanyl-tRNA-synthetase (anti-PL-12), two anti-ARS antibodies, were higher in RA patients with concurrent ILD (both p<0.05). Myositis and ILD worsening were not observed in three anti-ARS antibody- positive patients despite biological disease modifying antirheumatic drug administration. There was no difference in anti-cyclic citrullinated peptide and rheumatoid factor specificities between patients with or without ARS antibodies. Conclusion: Anti-ARS antibodies were detected in RA patients, with higher prevalence in patients with concurrent ILD. RA patients, specifically those with ILD complications, should be tested for anti-ARS antibodies.